Projectile coherence: The Van Cittert - Zernike theorem revisited. (July 2015) - Fabre, I; Navarrete, F; Sarkadi, L; Barrachina, R O
Synopsis: We study the time evolution of an incoherent mixture of identical particles by solving the Liouville - von Neumann equation for the corresponding density matrix. We demonstrate the quantum mechanical equivalent of van Cittert - Zernike theorem, and apply these results to the quantitative analysis of the coherence of a beam of particles in atomic collisions.